Modeling and evaluation of cyber‐physical systems in civil engineering. Issue 1 (15th March 2018) - Legatiuk, Dmitrii; Dragos, Kosmas; Smarsly, Kay
Abstract: A cyber‐physical system (CPS) is a coupled system integrating computing, networking, and physical processes. Through actuation, cyber‐physical systems control the physical processes, usually with feedback loops, where the physical processes affect computing and networking processes, and vice versa. In civil engineering, the most common fields of CPS applications are structural health monitoring (SHM) and structural control. A typical CPS task is the assessment of a structure based on (i) collected measurement data and (ii) a corresponding model. However, for an accurate and precise assessment of a structure, the CPS itself must be modeled and evaluated. In this paper, a conceptual modeling and evaluation approach is proposed, in which each part of a CPS is evaluated individually. In this study, the conceptual approach is presented for modeling and evaluation of CPS in civil engineering. The evaluation is based on an abstract approach allowing a discussion of a principle (i.e. general) model structure of a CPS, identifying critical issues to be studied in more detail in future research. (© 2017 Wiley‐VCH Verlag GmbH & Co. KGaA, Weinheim)